An innovative agile model of smart lean-green approach for sustainability enhancement in industry 4.0 - Varun Tripathi; Somnath Chattopadhyaya; Alok K. Mukhopadhyay; Shubham Sharma; Jujhar Singh; Danil Yu. Pimenov; Khaled Giasin (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Industry 4.0 emphasizes developing an innovative approach to eliminating the problems caused by environmental and shop floor waste, which is accomplished by a suitable process optimization approach. The process optimization approach is used to maximize productivity within limited constraints by observing end-to-end management systems. The present research work developed an innovative agile model using the lean, smart, and green approach to improve operational performance within limited constraints in Industry 4.0. The proposed model was developed by thoroughly reviewing research articles conducted over the past decades on process optimization approaches that include lean manufacturing, smart manufacturing, kaizen, and lean six sigma. The model was validated through two real production case studies in the mining machinery and automobile industries. The present article concluded that overall operational performance was enhanced in both case studies by improvement in different factors, including working environment, worker efficiency, environmental evolution, logistics management, and resources utilization. The authors of the present article strongly believe that the proposed innovative agile model would help people in industry make aesthetic and smart sustainable production systems in Industry 4.0 within limited constraints.
Keywords: 650; environmental impacts; green manufacturing; industrial sustainability; Industry 4.0; lean manufacturing; process optimization approach